2008
DOI: 10.1111/j.1464-410x.2008.07792.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of large adrenal tumours: the University of Miami experience using liver transplantation techniques

Abstract: OBJECTIVE To report our experience in the surgical management of patients with large adrenal masses and describe the key steps in performing radical resections, which are especially demanding where thrombi extend into the inferior vena cava (IVC). PATIENTS AND METHODS From 2003 to 2007, 14 patients presented with large adrenal mass, and underwent surgical extirpation. In five patients thrombi extended into the IVC, causing Budd–Chiari syndrome in one. RESULTS The median (range) patient age was 48  (40–58) year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Adrenocortical carcinoma (ACC) and upper tract urothelial carcinoma are also known to involve the IVC. In 2008, Delis et al reported on the experience at UM/JMH managing 14 patients with extensive ACC [32]. In total, 5 (35.7%) patients had tumor invading the IVC and were successfully treated with tumor thrombectomy.…”
Section: Experience At Um/jmhmentioning
confidence: 99%
“…Adrenocortical carcinoma (ACC) and upper tract urothelial carcinoma are also known to involve the IVC. In 2008, Delis et al reported on the experience at UM/JMH managing 14 patients with extensive ACC [32]. In total, 5 (35.7%) patients had tumor invading the IVC and were successfully treated with tumor thrombectomy.…”
Section: Experience At Um/jmhmentioning
confidence: 99%
“…Renal and adrenal tumors infrequently extend into the inferior vena cava (IVC) (1,2). Unfortunately, surgery remains the only potential cure for these patients (3,4). Most surgeons would agree that this type of surgery is complex and require an excellent understanding of the anatomy (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, surgery remains the only potential cure for these patients (3,4). Most surgeons would agree that this type of surgery is complex and require an excellent understanding of the anatomy (4,5). The surgical technique has to provide adequate exposure and optimal vascular control to avoid perioperative complications, including massive hemorrhage and death.…”
Section: Introductionmentioning
confidence: 99%
“…However, in cases where the tumors are considered to be unresectable in situ, such as when tumor invasion to the IVC or the liver is evident, or the tumor is located between the IVC and the portal triad, ex vivo resection of the tumor and autotransplantation of the liver is an option (10). Increased surgical experience with liver transplantation has enabled surgeons to perform such a complex procedure (11,12). Using the TTIVC technique, we believe that venous bypass is not necessary because venous flow of the liver into the IVC is completely preserved during TTIVC.…”
Section: Discussionmentioning
confidence: 99%